The socio-psychological predictors of support for post-truth collective action. Issue 4 (4th July 2022) - Mashuri, Ali; Putra, Idhamsyah Eka; Kavanagh, Christopher; Zaduqisti, Esti; Sukmawati, Fitri; Sakdiah, Halimatus; Selviana, Selviana
ABSTRACT: Politics in the current era are replete with unreliable media stories which lack evidence, sometimes disparagingly dubbed "fake news". A survey on a sample of Muslims in Indonesia ( N = 518) in this work found that participants' endorsement of collective action in of support issues with little to no empirical evidence (i.e., post-truth collective action) increased as a function of their belief in fake news and prejudice against the outgroup (i.e., non-Muslims). Belief in fake news stemmed from participants' generic and specific conspiratorial thinking, whereas prejudice was positively predicted by relative Muslim prototypicality, denoting how much Muslims in Indonesia view that their group is more representative than non-Muslims of the superordinate Indonesian identity that encompasses both groups. Additionally, our findings revealed that generic conspiratorial thinking and relative Muslim prototypicality were positively predicted by collective narcissism, which in turn spurred participants' support for collective action by augmenting belief in fake news.